Analisis Pengelolaan Dana Desa Terhadap Kinerja Perangkat Desa Dalam Aspek Efektivitas dan Efesiensi Pada Desa Banjarejo Kecamatan Batanghari Kabupaten Lampung Timur - Amalia Ramadhani; Erni Eka Setiawati; Muthie Apriyanti; Nurul Syamsiyah; Carmidah Carmidah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to analyze village financial management in terms of efficiency and effectiveness based on the performance of the village head in Banjarejo Village, Batanghari District, East Lampung. Village officials should be transparent in managing the village budget APBD in accordance with the principles of accountability, participation and budget responsibility. Village financial management includes planning, implementation, management and reporting stages. The village head's performance is measured using indicators of productivity, service quality, participation, responsibility and accountability. The number of research methods used is explained, and the research subject is the Head of Banjarejo Village. Primary data was obtained through direct interviews with village heads, while secondary data was obtained from books. Good and fair forecasts are made based on budget figures and determination of village income and expenditure in 2022 and 2023. The research results show that productivity reaches 100% in 2022 and 2023, which means the village head's performance is effective. The efficiency level which reaches 100% in 2022 shows good performance, but falls to 89% in 2023 which shows good performance. This situation shows that village fund management must be improved for the success of village funds.